Response surface methodology approach for optimization of growth and nutrient composition of kenaf (hibiscus cannabinus L.) cultivar by liquid bio-fertilizer application - Abdul Aziz, Muhammad Salman (2020)
Feedstuff is an important input to sustain a livestock production. In Malaysia, animal feed for ruminant livestock, especially forages, are often inadequate in term of nutrients value. Kenaf (Hibiscus cannabinus L.) has been viewed as a potential alternative crop in the Malaysian agriculture in recent years for animal feeds. This study was conducted to evaluate the effect of plant maturity, planted density and soil fertility on morphological growth and nutrient composition of kenaf and to determine their optimum values by using RSM (Response Surface Methodology). In order to determine the optimum plant maturity denoted as (X1), plant density, (X2), and bio-fertilizer application rate, (X3), a field experiment was carried out based on Central Composite Design (CCD) that fit a second order polynomial by a least squares technique and developed an equation that was used to describe how these variables effect the responses. The interrelationship among the variables were also determined. Three levels for each factor, X1 (28 days, 42 days and 56 days), X2 (100,000 plants/ha, 300,000 plants/ha and 500,000 plants/ha) and X3 (30 kg N/ha, 60 kg N/ha and 90 kg N/ha) were selected to investigate the influence and interaction between these factors. The results showed that plant maturity had a significant (P<0.01) effect on kenaf plant height, yield, ash, OM, CP and ADL. For plant density, there was a significant (P<0.05) effect on kenaf plant height with no significant effect on other dependent variables. Whereas, fertilizer rate had significant (P<0.05) effect on kenaf plant height, yield and CP with no significant effect on other dependent variables. When optimization model and equations were developed by RSM based on obtained results (plant maturity = 28 days, plant density = 430,000 plants/ha and bio- fertilizer rate = 90 kg N/ha), another field experiment was conducted to validate the model. The validation experiment is vital to demonstrate evidences that a procedure, model and equations carried out in RSM are true within the system. The optimum plant density, plant maturity and bio-fertilizer rate were applied to the growing kenaf during validation experiment to get its optimum morphological growth and nutrient composition values, which is suitable for ruminant livestock feeds. The effect of 28 days of plant maturity, 430,000 plants/ha of plant density and 90 kg N/ha of bio-fertilizer rate in validation experiment does positively affect the morphological growth (height and number of leaves; except for kenaf yield) and nutrient composition of kenaf (DM and CP; except ash, OM, ADF, NDF and ADL) in actual values when comparing them to predicted values. The results indicate that both bio-fertilizer rate and plant density positively affect kenaf plant growth in term of height, but the plants were more influenced by liquid bio-fertilizer rate even though the plant is still considered young to give any major morphological effect. These values are suitable and more likely to be used for ruminant livestock feed.